VO#039 Variation for plumbing and electricity works rev.01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of revised variation for plumbing and electricity works of BRACU new campus project.